Physical-chemical, thermal and mechanical performance of a polymer blend based on babassu coconut mesocarp starch (Research, Society and Development, 2023)
The objective was to characterize the physical-chemical, thermal and mechanical properties of a polymer blend based on babassu coconut mesocarp starch, with the addition of glycerin, melamine/formaldehyde. The babassu coconut mesocarp was used as raw material and the plasticizers glycerin, melamine/formaldehyde were added. Thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR), Visible Ultraviolet (UV-Vis), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and traction. The polymer blend showed non-homogeneous distribution with irregular and rough undulations, small differences in color and melamine concentrates, presence of starch residues, without pores and fissures. TGA revealed that the degradation ranges of starch and most organic compounds ranged from 210 ºC to 400 ºC. The DSC showed a predominance of endothermic events. The FTIR identified the starch present and the peaks of melamine and glycerin compounds. UV-Vis showed maximum lengths between 220 and 247 nm, and an accentuated shoulder at 281 nm referring to the electronic transitions of the double bonds present in melamine and starch. The blend is amorphous, with points of crystallinity due to starch and/or overlapping with melamine. The tensile mechanical behavior was of the ductile type. It is concluded that the proposed methodology for the formation of a polymer blend based on babassu coconut mesocarp starch showed good results for physical-chemical, mechanical and thermal properties, being an innovative product with possible potential for different applications.